A double-phase field model for multiple failures in composites. (1st August 2022) - Zhang, Peng; Tan, Siyuan; Hu, Xiaofei; Yao, Weian; Zhuang, Xiaoying
Abstract: Fiber reinforced composites have very excellent mechanical properties due to their sophistic microstructures. At the same time these microstructures can induce complex failure mechanisms including intralaminar damage, interlaminar damage and the interactions between them. Nevertheless, high fidelity simulations for these complex failure mechanisms are still challenging. In this paper, we develop a double-phase field model for complex failure in fiber reinforced composite. In the model, two different phase fields, i.e., fiber phase field and matrix phase field, are adopted for characterizing fiber damage and matrix damage, respectively. The failure mechanisms of fiber damage as well as the other modes in matrix damage are identified through a new strain energy density form that contains four different effective strain variables as well as a new effective constitutive tensor. Then by coupling with redefined degradation functions corresponding to different failure mechanisms, specified damage initiation and evolution criteria can be embedded into the proposed model automatically. Moreover, the new model is implemented in an explicit manner. The proposed model is verified and validated through the comparison between the predicted results and that of the experiments on the failure in unidirectional block and composite laminate.